Features of thermo-mineral waters of Višegrad Spa and their therapeutic application - Dušana Bukvić; Igor Sladojević; Siniša Ristić (Биомедицинска истраживања, 2014)
Scientific evidence has suggested significant physiological changes in the human body, after the ap plication of thermo-mineral water, either by drinking or using the local water. The paper presents the properties, methods and possibilities of application of thermal mineral waters in Visegrad Spa. Water of Visegrad Spa is categorized as calcium, magnesium, hydro carbonated, homeothermic mineral, oligo, radon water. The effect of water on the body can be thermal, mechanical and chemical. Homeothermic water has beneficial effect on the cardiovascular system, emphasizing the positive effects of the gas radon. It is believed that radon activates the hypothalamus-pituitary-adrenal axis and increases secretion of glucocorticoids, exerting its numerous effects on the body. Radon water exerts the strongest analgesic effect of all thermal mineral waters.
Keywords: termomineral water; radon; Višegrad spa